Postoperative management of portal vein arterialization: an interdisciplinary institutional approach - Majlesara, Ali; Golriz, Mohammad; Ramouz, Ali; Khajeh, Elias; Sabetkish, Nastaran; Wielpütz, Mark Oliver; Rio Tinto, Hugo; Abbasi Dezfouli, Sepehr; Loos, Martin; Mehrabi, Arianeb; Chang, De-Hua (Cancers, 2024)
Portal vein arterialization (PVA) is a surgical procedure that plays a crucial role in hepatic vascular salvage when hepatic artery flow restoration remains elusive. Dedicated diagnostic vascular imaging and the timely management of PVA shunts are paramount to preventing complications, such as portal hypertension and thrombosis. Regrettably, a lack of standardized postoperative management protocols for PVA has increased morbidity and mortality rates post-procedure. In response to this challenge, we developed a PVA standard operating procedure (SOP) tailored to the needs of interventional radiologists. This SOP is designed to harmonize postoperative care, fostering scientific comparability across cases. This concise brief report aims to offer radiologists valuable insights into the PVA technique and considerations for post-PVA care and foster effective interdisciplinary collaboration.
Gesehen am 13.01.2025